Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
An opportunity to investigate the applications of vibrant matter in an architectural context arose from an invitation to collaborate on the Hylozoic Ground installation by Philip Beesley. This chapter, therefore, examines the conditions in which vibrant matter and different species of ELT such as the Bütschli system can be applied and orchestrated, using morphological computing approaches within an architectural design setting. General design principles were developed for the installation with potential applications for broader architectural design contexts. A series of design experiments were also conducted to establish an approach towards developing appropriate infrastructures that may enable and prolong the lively action of vibrant matter.